1996
DOI: 10.1021/jo951746w
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Additions toanti-Sesquinorbornene. Br2in Methanol and the Addition of Acetic Acid

Abstract: The kinetics and products of addition of Br2 in MeOH to anti-sesquinorbornene (1) have been studied at 25 °C in the presence of varying [LiBr]. The products consist of ∼10% cis dibromide and 90% cis methoxy bromide, the amounts of these being independent of the [Br-]. The kinetics reveal that the reaction proceeds via the addition of Br2, and that Br3 - is not a brominating agent for this olefin. Acetic acid is shown to add rapidly to the double bond of 1 in a spontaneous reaction and via an acid-catalyzed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…-10 10 M -1 s -1 ), and the observed lack of such, a lifetime of 10 -11 s for the ionic forms was suggested. 36 This value is slightly less than the experimentally determined lifetimes of 10 -9 -10 -10 s for the bromonium ions of cyclohexene, cyclopentene, tetramethylethylene, and styrene in methanol.…”
Section: Beyond the Bromonium Ion: Hindered But Reactive Olefinsmentioning
confidence: 72%
“…-10 10 M -1 s -1 ), and the observed lack of such, a lifetime of 10 -11 s for the ionic forms was suggested. 36 This value is slightly less than the experimentally determined lifetimes of 10 -9 -10 -10 s for the bromonium ions of cyclohexene, cyclopentene, tetramethylethylene, and styrene in methanol.…”
Section: Beyond the Bromonium Ion: Hindered But Reactive Olefinsmentioning
confidence: 72%
“…In an earlier report, we have indicated that the β-bromocarbocation of 1 must have a lifetime of less than 10 -11 s in methanol. This was based on our inability to detect changes in the dibromide/methoxy bromide product ratio (∼10/90) as a function of added LiBr up to a concentration of 0.3 M. Although the solvent system here is different, it might be expected that the lifetime of a protonated 1 ( 1- H + ), in an aqueous medium, might be similar or slightly less than this.…”
Section: Discussionmentioning
confidence: 88%
“…Ethylene glycol dimethyl ether (DME, Aldrich, 99.9%, HPLC grade) was used with no further purification. LiClO 4 was purified as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations